A Content Analysis of the Text Readability in the Textbook Endorsed by the Government - Azmi, Aulia (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
Material is an important component of teaching to create a successful teaching and learning process. The purpose of this study is to describe the content of reading material in “Bahasa Inggris” textbook which endorsed by the government, especially the readability of the reading texts. This study used a descriptive content analysis method to analyze, interpret, and describe the data of the textbook. Moreover, the instruments for analyzing the readability of the texts were How Many Syllables program and Flesch Reading Ease formula. The result showed that the research finding dealt with readability level of the texts in the textbook which was categorized into three categories. Firstly, the texts were categorized as readable, but they were under the expected level of the tenth grade with a percentage of 62.5. Secondly, the texts were categorized as readable, and they were intended for the tenth grade students with a percentage of 12.5. Thirdly, the texts were categorized as not readable because they were above the expected level with a percentage of 25. Based on this research finding, it can be concluded that How Many Syllables program and Flesch Reading Ease formula can help the teachers to provide appropriate reading material for students.